Mediating Role of Knowledge and Moderating Role of Subjective Norm: Theory of Reasoned Action Approach to Keris Sumenep - Hafidhah; Purwanto, Edy; Herli, Mohammad (Ilomata International Journal of Social Science, 2025)
Keris is one of the objects of study that is very interesting to study. The research develops a model from the theory of reasoned action using knowledge variables as mediating and moderating variables and subjective norms as moderating variables. This research aims to determine the influence of attitude on purchase intentions, the influence of knowledge as a mediating and moderating variable, and subjective norms as a moderating variable. This study uses a quantitative approach. This research was conducted in Sumenep. The object used in this research is Keris. Two hundred respondents were taken using a purposive sampling method. Hypothesis testing was done using simple linear and hierarchical regression analyses for moderation and mediation tests. The findings of this research show that attitude has a significant effect on knowledge and consumer purchasing intentions. Consumer knowledge also has an important influence on purchase intention. The knowledge variable moderates and mediates the influence of attitude on consumer purchase intention. The subjective norm does not moderate the influence of attitude on purchase intention. This research concludes that attitude notably influences knowledge and intention to make purchases. Knowledge can moderate and mediate the influence of attitude on consumer purchase intentions. The subjective norm variable does not moderate the influence of attitude on purchase intention. This research provides additional studies regarding the TRA theory by adding the knowledge variable as a moderating variable and the subjective norms as moderating variables.